2014
DOI: 10.1590/s1679-45082014ao3131
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial infections by Klebsiella pneumoniae carbapenemase producing enterobacteria in a teaching hospital

Abstract: Objective To analyze the profile of patients with microorganisms resistant to carbapenems, and the prevalence of the enzyme Klebsiella pneumoniae carbapenemase in interobacteriaceae.Methods Retrospective descriptive study. From the isolation in bacteriological tests ordered by clinicians, we described the clinical and epidemiological characteristics of patients with enterobacteria resistants to carbapenems at a university hospital, between March and October 2013.Results We included 47 isolated patients in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1
19

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 15 publications
3
22
1
19
Order By: Relevance
“…w przeprowadzonej analizie zakażeń szpitalnych powodowanych przez pałeczki Enterobacteriaceae produkujące karbapenemazy. Wykazali oni, że bakterie te były izolowane głównie z wydzieliny oskrzelowej (25%), moczu (21%) oraz krwi (11%) [21].…”
Section: Dyskusjaunclassified
“…w przeprowadzonej analizie zakażeń szpitalnych powodowanych przez pałeczki Enterobacteriaceae produkujące karbapenemazy. Wykazali oni, że bakterie te były izolowane głównie z wydzieliny oskrzelowej (25%), moczu (21%) oraz krwi (11%) [21].…”
Section: Dyskusjaunclassified
“…In addition, this resistance mechanism has high potential for dissemination due to its plasmid location, which facilitates transfer to the interspecies gene. Therefore, KPC has been identified in several other Enterobacteriaceae and nonfermenting Gram-negative bacilli ( Acinetobacter baumannii and Pseudomonas aeruginosa ) 3, 4…”
Section: Introductionmentioning
confidence: 99%
“…[16] Seibert et al in their study in Brazil found K. pneumoniae was the microorganism that presented with the greatest resistance to carbapenems ( 62.0%). [17] Praveen et al, 2010 studied K. pneumoniae, from 134 clinical isolates about 43.6% percent isolates were resistant to Meropesnem. (Praveen et al, 2010).…”
Section: Discussion:-mentioning
confidence: 99%